PROBLEMS AND PROSPECTS OF THE DEVELOPMENT OF THE HOTEL INDUSTRY OF UKRAINE IN WAR CONDITIONS - VLASENKO, Ivan; MYKHALCHYSHYNA, Larysa; SHEVCHUK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Tourism occupies a significant share in the structure of the economy of many countries of the world and is one of the largest export industries. The hotel business, given its social direction, is extremely sensitive to the military and political situation in the country. The war in Ukraine caused a number of negative processes in the functioning of the country's hotel industry and forced hotel enterprises to adapt to modern realities. The article analyzes the state of activity of temporary accommodation and catering enterprises, outlines problems and prospects for the development of the industry. The dynamics of the number of collective means of accommodation in Ukraine in 2020-2023 are shown. The main difficulties and problems in the operation of hotel establishments with the beginning of a full-scale invasion are outlined. Significant changes in the activities of temporary accommodation facilities in Ukraine are caused precisely by the war, threats of attacks and destruction of the energy sector, disruption of supply chains, etc. Since the beginning of the war, the number of not only foreign tourists, but also domestic ones has decreased sharply. Hotel enterprises reoriented themselves mainly to the domestic consumer. Enterprises in the occupied territories closed or were annexed. Institutions that are located far from the combat zone have successfully reoriented themselves to providing health services, serving women with children, and people with disabilities. That is why the geography of domestic tourism has also changed. The distribution of collective means of accommodation (legal entities and individuals) by region of Ukraine is shown. The structure of collective means of accommodation in Ukraine in 2024 was analyzed. It is shown that the Ukrainian hospitality market demonstrates resilience even in the most difficult times. The country's tourism industry is recovering at the expense of domestic tourism, temporarily displaced persons and resettlement. Prospective directions of development of the hotel industry in today's realities are considered. An important factor in the successful operation of hotels is environmental sustainability and responsibility towards the environment. One of the ways to increase the environmental sustainability of resort hotels is the transition to the use of renewable energy sources. In general, in the future, work should be done on bringing the standards of the hotel industry closer to the standards of the European Union. Ukraine's tourism industry continues to recover, in particular thanks to the growth of domestic tourism and the gradual return of foreign visitors, including government delegations, international companies and volunteer organizations. Despite the difficult situation, the hotel business in Ukraine is adapting to today's challenges.
Keywords: tourism industry; collective accommodation facilities; hotel industry; hospitality market